Forensic Cyberpsychology and Approaches to Criminal Profiling - Vlajić, Dušan Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Although there are plenty of theories which consider psychological factors of criminal behavior and almost every criminal act has a digital aspect, criminal profiling is not so popular among forensic psychologists, especially when it comes to cybercrime. Thus, the goal of this paper is to give a brief overview of literature considering psychological factors which shape deviant computer and online behaviour. Two basic approaches of criminal profiling, inductive and deductive, will be presented, as well as their advantages, disadvantages, logic they follow and concepts they rely on when analysing digital evidence in order to narrow suspect pools. Concrete models developed under each approach will be briefly portrayed. Moreover, studies from the field of cyberpsychology will be presented and their relationship with profiling will be discussed, particularly with inductive approach, which is original contribution of this paper. At the very end, suggestions for overcoming limitations of previous studies and converging disciplines of criminal profiling and cyberpsychology will be offered.
Keywords: criminal profiling; inductive profiling; deductive profiling; cybercrime; cyberpsychology; digital evidence